Herpetofauna del sitio arqueológico Iglesia Vieja, Costa de Chiapas, México - López-Vila, Jesús M.; Torres-Meza, Arturo; Romero-Berny, Emilio I.; Pineda-Vera, Daniel (Instituto de Ecología, A.C., 2018)
A checklist of amphibians and reptiles in the archaeological site Iglesia Vieja was made. This site is located between the coast and the Sierra Madre of Chiapas at 711 masl. The samplings were carried out monthly between June 2014 and May 2015, covering the rainy and dry seasons in two types of vegetation (herbaceous and forested). The herpetofauna was represented by 61 species (12 amphibians and 49 reptiles). The amphibians were grouped into eight families, 10 genera and 12 species; for reptiles, the group of lizards was constituted by 13 families, 16 genera and 20 species; while snakes were represented by seven families, 25 genera and 29 species. The Jackknife 1 and Bootstrap richness estimators showed an adequate representation of the composition. The abundance curves showed a greater dominance of generalist or disturbance-associated species (Hemidactylus frenatus, Basiliscus vittatus, Rhinella horribilis). Thirty-five percent of the registered species is under some risk category according to federal regulations. Although the area is located in a physiographic transition zone, the herpetofauna showed a high affinity with the Pacific Coastal Plain (66.53%). The areas destined to preserve the archaeological heritage also constitute spaces that contribute to maintain the biological processes. These sites rarely have faunal inventories. This work represents a contribution to the knowledge of the associated biota with archaeological sites in Chiapas, and groundwork for the management and future research on the ecology of a priority group.